2020
DOI: 10.3390/cancers12010158
|View full text |Cite
|
Sign up to set email alerts
|

Stage IV Gastric Cancer: The Surgical Perspective of the Italian Research Group on Gastric Cancer

Abstract: Background/Aim: This work explored the prognostic role of curative versus non-curative surgery, the prognostic value of the various localizations of metastatic disease, and the possibility of identifying patients to be submitted to aggressive therapies. Patients and Methods: Retrospective chart review of stage IV patients operated on in our institutions. Results: Two hundred and eighty-two patients were considered; 73.4% had a single metastatic presentation. In 117 cases, a curative (R0) resection of primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…reported 5-year survival of 11.8%. 22 Although our results compare favourably to results of Ministrini et al ., some studies reported better long-term survival of up to 32% to 59%. 12 , 20 An important reason for better survival after liver resection in these repots might be that patients with metachronous liver resections were included.…”
Section: Discussionsupporting
confidence: 74%
“…reported 5-year survival of 11.8%. 22 Although our results compare favourably to results of Ministrini et al ., some studies reported better long-term survival of up to 32% to 59%. 12 , 20 An important reason for better survival after liver resection in these repots might be that patients with metachronous liver resections were included.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, the median participant age was 69 years, the median BMI was 20.3, and the median NLR was 3.15. These data are similar to those in previous studies for patients with stage IV gastric cancer [ 7 , 48 , 49 ]. In addition, the median survival time was 261 days in this study, comparable to the median survival time of less than 1 year that has been reported in patients with stage IV gastric cancer treated with chemotherapy [ 7 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…These data are similar to those in previous studies for patients with stage IV gastric cancer [7,48,49]. In addition, the median survival time was 261 days in this study, comparable to the median survival time of less than 1 year that has been reported in patients with stage IV gastric cancer treated with chemotherapy [7,49,50]. Thus, the characteristics of patients enrolled in our study were similar to those in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…According to the Japanese classification of gastric carcinoma, the presence or absence of residual tumor after surgery is defined as an R status [ 20 ]. Several studies have demonstrated that an R status is one of the most important prognostic factors in patients with advanced gastric cancer undergoing conversion surgery [ 21 24 ]. Yamaguchi et al had reported that the MST was 41.3 months and 21.2 months in patients with R0 and R1-2 resection undergoing conversion surgery after chemotherapy, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%